Experimental investigation of mini Gurney flaps in combination with vortex generators for improved wind turbine blade performance - Marinos Manolesos (Wind Energy Science, 2022)
This wind tunnel study investigates the aerodynamic effects of mini Gurney flaps (MGFs) and their combination with vortex generators (VGs) on the performance of airfoils and wind turbine rotor blades. VGs are installed on the suction side aiming at stall delay and increased maximum lift. MGFs are thin angle profiles that are attached at the trailing edge in order to increase lift at pre-stall operation. The implementation of both these passive flow control devices is accompanied by a certain drag penalty. The wind tunnel tests are conducted at the Hermann-Föttinger Institut of the Technische Universität Berlin based on two airfoils that are characteristic of different sections of large rotor blades. Lift and drag are determined using a force balance and a wake rake, respectively, for static angles of attack between −5 and 17∘ at a Reynolds number of 1.5 million. The impact of different MGF heights including 0.25 %, 0.5 % and 1.0 % and a VG height of 1.1 % of the chord length is tested and evaluated. Furthermore, the clean and the tripped baseline cases are considered. In the latter, leading-edge transition is forced with Zig Zag (ZZ) turbulator tape. The preferred configurations are the smallest MGF on the NACA63(3)618 and the medium-sized MGF combined with VGs on the DU97W300. Next, the experimental lift and drag polar data are imported into the software QBlade in order to design a generic rotor blade. The blade performance is simulated with and without the add-ons by means of two case studies. In the first case, the retrofit application on an existing blade mitigates the adverse effects of the ZZ tape. Stall is delayed and the aerodynamic efficiency is partly recovered leading to an improvement of the power curve. In the second case, the new design application allows for the design of a more slender blade while maintaining the rotor power. This alternative blade appears to be more resistant against the adverse effects of forced leading-edge transition.